Logística reversa de notebooks e periféricos: caracterização do fluxo domiciliar de geração e destinação na cidade João Pessoa/PB – Brasil - Brilhante, Anna Kryslene Viana Chianca (2023)
In recent decades, due to the rapid advancement of technology, the generation of waste electrical and electronic equipment (WEEE) has grown considerably. Among this equipment are notebooks and their peripherals, which make up a large part of the “electronic waste”. The household flow of WEEE is complex because it is associated with sociocultural habits and behaviors and its study is of fundamental importance to establish guidelines for its management. Thus, this work aimed to identify the household flow of generation and destination of notebooks and peripherals in João Pessoa/PB in order to provide information that contributes to the reverse logistics of its waste in the city. For this, data collection was carried out through contact with users of notebooks and peripherals in that city through a questionnaire. Then, the data were treated using spreadsheets, graphs and other statistical tools. In general, was noted the influence of the increase in consumption of electrical and electronic equipment (EEE) over time, the accelerated advancement of technologies and planned obsolescence in the household flow of generation and disposal of notebooks and peripherals in João Pessoa/PB. As for acquisition, it was found that 96.36% of respondents had notebooks in use, acquired mainly to meet the need for another notebook at home and through internet stores. As for storage, 34.81% had a notebook that had not been used at home, which operated mainly in the medium to long term and were mostly stored for less than 2 years. Among the stored peripherals, mouse, headset and keyboard predominated. The most frequent defects in notebooks in use and out of use were slowdowns and crashes and battery problems. The main reason for not seeking repair was the cost. Although the majority of respondents are aware of the substances harmful to health and the environment contained in electronic waste, most never disposed of parts, peripherals or notebooks at collection points, mainly because they were not aware of the existence of such points. The main suggestions/improvements proposed for the reverse logistics system for notebooks and peripherals in the city of João Pessoa/PB involved increasing the number of collection points, carrying out awareness campaigns on the disposal of WEEE, establishing partnerships with commercial establishments and analyzing the feasibility of charging for the separate collection of WEEE, upon payment of a fee by the population.